Evaluation of the mastoid air cell system by high resolution computed tomography: three-dimensional multiplanar volume rendering technique - (:unkn) unknown (CAMBRIDGE UNIV PRESS, 2003)
The mastoid air cell system is an important contributor to the pathophysiology of middle-ear inflammatory disease. The mastoid cavity is not only an air reservoir, but also an active space for gas exchange. Various methods of temporal bone imaging have been designed to investigate mastoid pneumatization. In this study, we examined 100 normal temporal bones for the evaluation of mastoid pneumatization. Mastoid air cell systems were measured by reconstructed axial and coronal high resolution computed tomography (HRCT) images. The reconstructions were made by a three-dimensional multiplanar volume rendering (3D MPVR) technique. The mean volume of the mastoid air cell pneumatization was 7.9 cm(3) (4.0-14.0 cm(3), SD = 2.3 cm(3)). The ears were allocated to the groups with respect to measured mastoid air cell pneumatization. Twenty-eight per cent of the ears have small pneumatization with an air cell system not exceeding 6 cm(3). Fifty-two per cent had an air cell system between six and 10 cm(3), and 20 per cent had an air cell system exceeding 10 cm(3). With its excellent imaging quality and the ability to eliminate bone and soft tissue, HRCT is the best method for evaluating the mastoid air cell system. The 3D MPVR technique must be used to measure the temporal bone/mastoid pneumatization for the best results.
Keywords: mastoid; X-ray tomography; computed; SECRETORY OTITIS-MEDIA; MIDDLE-EAR; PNEUMATIZATION; RETRACTION; SIZE